Penggunaan Metode Pembiasaan Dalam Program Sholat Dhuha Pada Anak Kelompok B5 TK Islam Sulthoniyah Sambas Tahun Pelajaran 2022-2023 - Susi Lestari (Tarbiya Islamica, 2024)
This research was conducted because of the phenomenon where there were children in the Sulthoniyah Sambas Islamic Kindergarten who did not want to follow the teacher's directions, namely the Dhuha prayer. This research aims to find out and describe: (1) Implementation of Duha prayers through the habituation method in group B5 children; (2) Ability to pray Dhuha in group B5 children; (3) Supporting and inhibiting factors in the Dhuha prayer program for children in group B5. This research uses a qualitative approach with a phenomenological type. Data sources in this research are teachers, group B5 children, school principals and documents relevant to the research theme. Data was collected using observation, interview and documentation techniques. The stages of data analysis carried out are data reduction, data display, and verification. The validity of the data was tested using data triangulation and member check techniques. The results of the research show that: (1) The implementation of the Dhuha prayer through the habituation method for children in group B5 has gone very well and is in accordance with their responsibilities as a teacher; (2) The ability to perform Duha prayers in group B5 children has developed according to the expected competencies both in the aspects of prayer movements and reading; and (3) Factors supporting the implementation of dhuha prayers for children in the B5 group at the Sulthoniyah Sambas Islamic Kindergarten are more dominantly influenced by teacher factors. The more dominant factor inhibiting the implementation of Duha prayers in group B5 children is the factor of parental attention.